ANOTHER syndrome—Familial presentations of progressive lung disease leading to double lung transplantation: A case report and literature review. Issue 12 (5th November 2021) - Thornton, Christina S.; Puttagunta, Lakshmi; Helmersen, Douglas; Thakrar, Mitesh V.; Nagendran, Jayan; Lien, Dale; Varughese, Rhea A.
Abstract: Ectodermal dysplasias (EDs) are a heterogeneous rare group of disorders with an incidence at 1/100, 000 live births. Currently, there are limited case reports of patients requiring lung transplantation. Here, we report two brothers who present with a constellation of features including alopecia, nail dystrophy, ophthalmic complications, thyroid disease, hypohidrosis, ephelides, enteropathy and recurrent respiratory tract infections, known as ANOTHER syndrome, a rare autosomal recessive variant of ED. Both presented in early childhood with progressive respiratory decline and eventual failure. Chronic respiratory decline was refractory to standard therapy. Both patients required lung transplantation for sequelae of end‐stage lung disease. Pathology demonstrated multifocal bronchiectasis with areas of fibrosis and small airway obstruction. ANOTHER syndrome is rare with a paucity of data in the literature. Given the limited therapeutic options available with natural progression towards respiratory failure, lung transplantation may be considered. Abstract : We report two brothers who presented with a constellation of features including alopecia, nail dystrophy, ophthalmic complications, thyroid disease, hypohidrosis, ephelides, enteropathy and recurrent respiratory tract infections, known as ANOTHER syndrome, a rare autosomal recessive variant of ectodermal dysplasia (ED). Both received lung transplantation, and we report their clinical course to highlight the sequelae of end‐stage lung disease of hypohidrotic EDs.